Pengaruh Lifestyle, Influencer Marketing , Dan Product Design Terhadap Keputusan Pembelian Produk Eiger - Eko Agus Alfianto; Kiki Zakiyah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to examine the influence of lifestyle, influencer marketing and product design on Eiger purchasing decisions. The population of this study is Eiger consumers who make purchases at outlets. This study uses a quantitative approach. The data collection technique was carried out by distributing questionnaires using the non-probability method with a purposive sampling technique to 100 respondents. The results showed that lifestyle has a positive and significant effect on purchasing decisions. The results of the study show that influencer marketing has a positive and significant effect on purchasing decisions. The results show that product design has a positive and significant effect on purchasing decisions. The results show that the lifestyle, influencer marketing and product design variables have a positive and significant impact on purchasing decisions.